2001
DOI: 10.1128/iai.69.12.7461-7470.2001
|View full text |Cite|
|
Sign up to set email alerts
|

Influence ofMycobacterium bovisBacillus Calmette Guérin on In Vitro Induction of CD1 Molecules in Human Adherent Mononuclear Cells

Abstract: Nonpeptide antigens (including glycolipids of microbial origin) can be presented to T cells by CD1 molecules expressed on monocyte-derived dendritic cells. These HLA unrestricted responses appear to play a role in host immunity against Mycobacterium tuberculosis and other pathogenic bacteria. It is known that vaccination with Mycobacterium bovis bacillus Calmette-Guérin (BCG) has limited efficacy in many clinical settings, although the reasons for its inadequacy remain unclear. Here we have investigated the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
(51 reference statements)
2
19
1
Order By: Relevance
“…Interestingly, it has been reported that forskolin treatment of GM-CSF/IL-4-derived dendritic cells have decreased CD1a expression, consistent with our cell line data (32). Similarly to CD1A, ATF/CREB family members can be altered in multiple sclerosis, various cancers, and M. tuberculosis-infected cells (14,15,(43)(44)(45)(46). Thus, examining alteration of ATF/CREB family members could lead to insight into CD1a expression, as well as function and activation of CD1a-restricted T cells.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Interestingly, it has been reported that forskolin treatment of GM-CSF/IL-4-derived dendritic cells have decreased CD1a expression, consistent with our cell line data (32). Similarly to CD1A, ATF/CREB family members can be altered in multiple sclerosis, various cancers, and M. tuberculosis-infected cells (14,15,(43)(44)(45)(46). Thus, examining alteration of ATF/CREB family members could lead to insight into CD1a expression, as well as function and activation of CD1a-restricted T cells.…”
Section: Discussionsupporting
confidence: 79%
“…CD1a expression is also altered in various human infections. Both bacillus Calmette-Guérin and Mycobacterium tuberculosis infection result in demonstrable change in CD1a, b, and c surface expression (15,16). In addition, a strong correlation between CD1 expression and effective host immunity in leprosy has been reported (17).…”
mentioning
confidence: 99%
“…Purified PEIPC, but not POVPC, recapitulated the inhibitory effects of oxPAPC on CD1 expression (Supplemental Figure 1D). Therefore, as with mycobacterial infection (31,32), PEIPC inhibited expression of CD1 molecules on differentiating DCs. In contrast, fractions enriched in PEIPC did not inhibit expression of MHC class II on monocyte-derived DCs ( Figure 4B).…”
Section: Figurementioning
confidence: 99%
“…A key cell of the innate immune system is the DC, whose differentiation can be followed by the expression of CD1 molecules, which are themselves antigen-presenting elements for lipid antigens to T cells. Previously, independent groups have shown that oxLDL (30) and mycobacterial infection (31,32) cause suppression of CD1 molecules on DCs. Furthermore, oxPAPC has been demonstrated to prevent the maturation of immature DCs (29).…”
Section: Figurementioning
confidence: 99%
“…These findings were interpreted as possible evidence of an immune evasion mechanism used by M. tuberculosis to avoid recognition through presentation of its antigens by CD1. Subsequent studies examining the effects of M. bovis BCG on the ability of CD1b to be induced on monocytes by exposure to GM-CSF also found evidence for inhibition of CD1 expression by live mycobacterial infection [11,12]. A similar downmodulation of group 1 CD1 expression and blockade of CD1 induction by GM-CSF has been shown to occur with infection of human monocyte-derived dendritic cells in vitro with the intracellular protozoan Leishmania donovani [13].…”
Section: Expression Of Group 1 Cd1 and Its Modulation By Infectionmentioning
confidence: 95%